Case Report: Atypical extensive orbitofacial tuberculosis extending to the skull base and cavernous sinus revealed major histocompatibility complex class II deficiency in an 11-year-old girl - Mezri, Sameh; Amri, Ameni; Essghaier, Sonia; Tlili, Karima; Rabhi, Maroua; Marmouri, Mahdi; Barakizou, Hager (Frontiers in Pediatrics, 2025)
BackgroundCavernous sinus tuberculosis is an extremely rare manifestation of central nervous system tuberculosis in children, with only two cases reported worldwide. It can mimic malignancy or other inflammatory conditions. Its occurrence in children with primary immunodeficiency, particularly major histocompatibility complex (MHC) class II deficiency, has not yet been described.Case reportWe report an 11-year-old girl with a history of recurrent infections and chronic otitis media. She presented with right orbital swelling, severe headaches, and exophthalmos. Imaging revealed an extensive mass in the sinonasal and orbital regions, extending to the skull base and cavernous sinus. A computed tomography-guided biopsy and histopathology, supported by PCR testing for Mycobacterium tuberculosis, confirmed extensive orbital and cervicofacial tuberculosis. An immunological evaluation and genetic analysis revealed familial MHC class II deficiency. The patient received anti-tuberculosis therapy [isoniazid, rifampin, pyrazinamide, and ethambutol (HRZE) followed by isoniazid and rifampin (HR)], leading to clinical and radiological improvement. She continues with intravenous immunoglobulin replacement therapy every 21 days while awaiting a bone marrow transplantation.ConclusionsThis case highlights the importance of considering tuberculosis in atypical cavernous sinus lesions in children, especially in endemic regions. Severe or unusual infections should prompt evaluation for underlying immunodeficiency.